Pengaruh OCB Terhadap Intensi Keluar Dan Kepuasan Kerja di RSU Bethesda Tomohon - Rumambi, Ferdy Toway (JURNAL RISET BISNIS DAN MANAJEMEN, 2013)
This study discusses the influence of Organizational Citizenship Behavior (OCB) on turnover intention and job satisfaction of medical nurses at Bethesda General Hospital Tomohon. Data collection method in this research is questionnaire with population as well as the sample as many as 180 medical nurses.Â  Data analysis method is simple linear regression. Research result shows that OCB (X) has no significant and negative influence on turnover intention (Y1) of medical nurses at Bethesda general hospital Tomohon. It means turnover intention of medical nurses at Bethesda general hospital Tomohon has no relationship with OCB behavior. Research result also shows that OCB (X) has significant and positive influence on job satisfaction (Y2) of medical nurses at Bethesda general hospital Tomohon. This research indicates that behavior of OCB performed by employees determine their job satisfaction. The more intense of OCB behavior, the higher job satisfaction is.